A study on the Porcine Respiratory Disease Syndrome (PRDC): Update review and proposed measures for its control. - GEORGAKIS (Α.Δ. ΓΕΩΡΓΑΚΗΣ), A. D.; BOURTZI-HATZOPOULOU (Ε. ΜΠΟΥΡΤΖΗ-ΧΑΤΖΟΠΟΥΛΟΥ), E.; KRITAS (Σ. Κ. ΚΡΗΤΑΣ), S. K.; BALKAMOS (Γ.Κ. ΜΠΑΛΚΑΜΟΣ), G. C.; KYRIAKIS (Σ.K. ΚΥΡΙΑΚΗΣ), S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Porcine Respiratory Disease Complex (PRDC) represents the major cause of economic loss for swine industry worldwide. It is a multifactorial syndrome with a wide variety in epidemiological features and clinical sings from farm to farm, depending on the prevalence of the responsible pathogens, the environmental conditions and the efficacy of the on-farm veterinary management. As a result, the identification of the pathogens involved is difficult to be established, along with the difficulty in applying an efficient control programme. Moreover, PRDC, is considered to be the most important cause of the extended use of antimicrobials in modern pig industry. Its control is based on the principles of the veterinary management applied from farm to farm, including the most appropriate hygienic, vaccination and metaphylaxis programmes. In this study, a review of the syndrome is presented (aetiology, epidemiology, pathogenesis, clinical signs, diagnosis) along with a short reference to its current status in Greece. Finally, essential measures for the greek pig industry and public health are suggested.